Danantara's Influence on State Economic Reform: A Review of Legal Theory and Public Investment Governance - Djayanti, Djayanti; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2024)
The purpose of this study is to examine the influence of Danantara on Indonesia’s economic reform from a legal theory perspective, while also exploring the legal implications for state financial governance and law enforcement, and the mechanisms ensuring transparency and accountability in public asset management. This research employs a qualitative doctrinal approach, integrating comparative and thematic analyses. Data were gathered from legal texts, policy documents, academic literature, and empirical studies to construct a comprehensive framework that situates Danantara within the context of legal development and modern governance practices. The study finds that the establishment of Danantara consolidates state asset management, thereby reducing bureaucratic inefficiencies and transaction costs, while enhancing fiscal discipline and strengthening legal oversight. Additionally, the research reveals that adaptive regulatory reforms and integrated digital monitoring systems are critical in ensuring that Danantara operates in alignment with national legal standards. Unlike previous studies, this paper uniquely integrates doctrinal, comparative, and thematic perspectives to offer a holistic legal framework for institutional reform. It bridges theoretical insights and practical applications, thereby providing a novel approach to understanding the role of centralized asset management in emerging economies.